Internet of energy things and its key technologies - Junyong LIU; Li PAN; Mai HE (物联网学报)
The rapid development of the Internet of things technology provides beneficial support for the energy transition.The deep integration of the Internet of things and various fields of energy has formed the Internet of energy things,which has become the basis of the development of the energy Internet.Firstly,the meaning of the Internet of energy things and its multi-dimensional differences compared with traditional energy networks were analyzed.The architecture of the Internet of energy things was designed.Secondly,several key technologies of the Internet of energy things were discussed.And then the related application of scenarios the Internet of energy things were proposed.Finally,the development prospects and challenges of the Internet of energy things were looked forward to.Hope that a useful reference for the subsequent practice and the in-depth research of the Internet of energy things was provided.